Codes mixing between buyers and mobile phone hackers in Bekasi, West Java - Jannes Freddy Pardede (Politeknik Negeri Bali, 2017)
This review discusses the code mixing that occurs on talks between a sales clerk and four buyers at a mobile phone shop located in a business centre in the central Bekasi, West Java. The data collection is done by recording conversations between four buyers and one the store saleswoman. Data was analysed qualitatively to obtain a comprehensive research result that aims to determine the type, level, nature, and causal factors of code interference. The results showed: (1) There are three types of code mixings that occur, namely external code-mixing, internal code-mixing and mixed code-mixing. The most common is external code-mixing, especially from English to Indonesian language. (2). The most common form of code-mixing is ​​in the word level. (3). The cause of code interference is caused by several factors, namely the limitation factor in the mastery of vocabulary in the source language, to show the familiarity and habit factor of the speaker.